Moulding graduates’ employability skills through problem-oriented project-based learning - Fatmawati, Latada; Hafizoah, Kassim; Jamilah Bebe, Mohamad; Mansor, Sulaiman (Universiti Malaysia Pahang, 2018)
This paper discusses the implementation of Problem-Oriented Project-Based Learning (POPBL) as part of I-LEAD intervention program at a public university. The I-LEAD program, which integrated soft skills theoretical knowledge and its application, was developed to help graduating students improve their employability skills before embarking into the working world. A one-group pre-test post-test experimental method was employed through the administration of an achievement test, perception questionnaire and student data from the university’s Integrated Management System. Thirty-two students who did not achieve the Program Objectives related to leadership skills, team working, communication skills, critical and problem solving and ethics and moral professional were recruited from various faculties. They were required to attend the program specifically the POPBL module. During the program, the students were grouped into a 5-member group to work on a project, write a proposal and final report, and present the project. The findings depict that students were able to prepare a project report, but needed guidance in preparing project proposal particularly in identifying a problem. Interestingly, most participants reported an adequate Soft Skills enhancement particularly team working and communication skills.